2005
DOI: 10.1111/j.1365-2990.2005.00676.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of matrix metalloproteinases in denervated muscle

Abstract: In a nerve crush model of denervation, we examined muscle matrix metalloproteinase (MMP) expression, localization and activity. In normal muscle, MMP mRNA levels were low, and immunohistochemically MMPs were distributed around the muscle fibre with MMPs-3, -7 and -9 also staining at the neuromuscular junction. Seven days after nerve crush, muscle MMP immunoreactivity, especially MMP-12 and MMP-14, became irregularly distributed. At 20 days reinnervation of the muscle was observed, and some restitution of the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 41 publications
2
30
0
Order By: Relevance
“…The main hypothesis explored in this study was that the differential regeneration ability of fast (EDL) and slow twitch (Soleus) muscles might result from differential MMPs action in ECM remodeling. In our current study we extended previous analyses of MMPs (Demestre et al, 2005) to the study of the localization of MMP-9 and MMP-2. Our results confirm that in the intact muscles only a weak immunostaining signal for MMP-9 and MMP-2 was detected around muscle fibers.…”
Section: Differences In Mmp-9 and Mmp-2 Mrna Expression During Differmentioning
confidence: 61%
See 2 more Smart Citations
“…The main hypothesis explored in this study was that the differential regeneration ability of fast (EDL) and slow twitch (Soleus) muscles might result from differential MMPs action in ECM remodeling. In our current study we extended previous analyses of MMPs (Demestre et al, 2005) to the study of the localization of MMP-9 and MMP-2. Our results confirm that in the intact muscles only a weak immunostaining signal for MMP-9 and MMP-2 was detected around muscle fibers.…”
Section: Differences In Mmp-9 and Mmp-2 Mrna Expression During Differmentioning
confidence: 61%
“…The invading inflammatory cells have the ability to release MMPs (Schoser et al, 2002). On the other hand, it has been demonstrated that MMP-9 is up-regulated during nerve crush whereas its level decreases when the muscle becomes reinervated (Demestre et al, 2005). In our crush induced regeneration model, Soleus myolysis was rapid, extensive and heterogeneous and accompanied by increase in blood flow when compared to EDL muscle.…”
Section: Differences In Mmp-9 and Mmp-2 Mrna Expression During Differmentioning
confidence: 78%
See 1 more Smart Citation
“…In denervated muscle, especially in the early phases when it has not yet been reinnervated, there is little information about the role of MMPs and TIMPs. Whereas several kinds of MMP were studied using gene expression (7), enzymatic activity (7), and localization by immunohistochemistry at muscle fibers, neuromuscular junctions, vessels, nerves, and fibroblast-like cells (7,15,21), the expression of TIMPs has never been examined in previous studies. In accordance with the findings that MMP-2 mRNA expression and immunohistochemical localization were unchanged up to 30 days after denervation or reinnervation (7,15), our results showed no significant modification of MMP-2 mRNA expression by denervation.…”
Section: Referencesmentioning
confidence: 99%
“…Changes in expression of MMPs and TIMPs were reported in skeletal muscles under hyper-and hypo-active conditions such as joint immobilization (1), unloading (8), tenotomy (26), and running (16). In denervated muscles, the mRNA or protein level expression of MMPs has been investigated in several studies (7,15,21); however, no results are available about the effects of TIMPs. In this study, we investigated the expression of fibrosis-related proteins, collagens (total, type I, and type III), TGF-β1, MMP-1, MMP-2, TIMP-1, and TIMP-2 in the early phases of denervation in the rat soleus muscle.…”
mentioning
confidence: 99%